Impact of Board Traits and Ownership form on Investment Efficiency: A study on Pakistan’s Food Sector (KASBIT Business Journal, 2020)
The motive behind this study was to assess the link of board traits and ownership form with investment efficiency of corporations. Fourteen firms were selected from food sector and their annual data for the time period 2009 to 2018 was collected from the annual reports. Richardson (2006) model was used to measure investment efficiency. Moreover, fixed effects panel data regression was employed to analyze data. Results indicate that investment efficiency improves with large board size, high proportion of managerial ownership, low proportion of block holder ownership and high proportion of institutional ownership. Overall results suggest that board traits and ownership form influences investment efficiency. This study is unique as it investigated the link of board traits and ownership form with investment efficiency in respect of Pakistan’s food sector firms. Results of this paper are valuable for investors as they desire to own firms that make efficient investment decisions. Thus, investors can ascertain the level of investment efficiency of corporations by considering the findings documented in this paper. This study focused on only food sector of Pakistan, so the link of board traits and ownership form with investment efficiency can be investigated for other financial and non-financial sectors of Pakistan in future.
Keywords: Ownership form, board characteristics, investment efficiency, corporate governance, Pakistan; Ownership form; board characteristics; investment efficiency; corporate governance; Pakistan